Feline coronavirus-associated myocarditis in a domestic longhair cat. Issue 2 (October 2019) - Ernandes, Maria A; Cantoni, Anna M; Armando, Federico; Corradi, Attilio; Ressel, Lorenzo; Tamborini, Alice
Case summary: A 9-month-old entire male domestic longhair indoor cat presented with a 3-week history of fluctuating fever, weight loss and small intestine diarrhoea, which was unresponsive to antibiotics and supportive treatment. Abdominal ultrasound revealed severe jejunal and ileocolic junction intestinal wall thickening with loss of layering. An enterectomy was performed and histopathology revealed severe pyogranulomatous enteritis with vasculitits, compatible with the diagnosis of feline infectious peritonitis (FIP). Four days after surgery, the cat re-presented with anorexia and acute onset of expiratory dyspnoea. Echocardiography showed left ventricular hypertrophy and bilateral atrial enlargement. Congestive heart failure caused by hypertrophic cardiomyopathy was suspected and treatment with furosemide was started, which led to amelioration of the clinical signs. The following day, four-limb ataxia, hypermetria and bilateral uveitis were evident. Given the persistent anorexia and worsening of the clinical signs, the cat was humanely euthanized and a post-mortem examination was performed. Necropsy revealed multifocal pyogranulomatous lesions involving multiple organs (adrenal glands, kidneys, lungs, brain, myocardium, lymph nodes, liver), compatible with the diagnosis of FIP. Immunohistochemistry performed on the myocardium revealed feline coronavirus-positive macrophages associated with pyogranulomatous lesions, justifying a diagnosis of feline coronavirus-associated myocarditis. Relevance and novel information: To the authors' knowledge, the case described here represents the first published report of feline coronavirus-associated myocarditis. This should be considered as a possible differential diagnosis in cats presenting with cardiac-related signs and other clinical signs compatible with FIP.